Voice Based Employee Management System Using AWS and Alexa (International Journal of Innovative Research in Computer Science & Technology, 2020)
In the developing and creating world,  everything is getting advanced, digital, computerized, and  automated. With an oversized number of labor  opportunities, the Human workforce has increased. Thus,  there is a need for a system that can handle the information  of such a large number of employees in a company. This  project untangles the task of maintaining records and data  of employees, thanks to its user-friendly GUI. The  “EMPLOYEE MANAGEMENT SYSTEM using AWS"  has been created to abrogate the issues with the existing  manual framework. This application is designed in such a  simplest way that it can eliminate and in some cases reduce  the efforts faced by the live system. Moreover, this method  is meant for the actual need of the corporate to holdout  operations smoothly and effectively. A Voice command  feature is additionally added to the system to avoid a waste  of time. The application is coded in such a way that, it  avoids mistakes while entering the data. It notifies the  employee/admin if he entered the incorrect, or invalid data. No formal knowledge or special training is required by the  employee/admin to use this application. Thus, it is  approved as an easy to understand and person-friendly  utility. The Voice command feature is additionally  straightforward to use and informative. This project will  allow admin to feature new employees after proper  authentication (manual). Admin can even edit departments  and posts (in a variety of bands). The database should store  all personal details of employees like date of birth, full  name, people, address, etc. this method enables employees  to fill their time-sheets daily or at intervals. The admin can  approve or reject the time-sheet filled by a worker together  with remarks. Admin may make workdays, Performance  charts, Leave details, and will edit employee details. An  employee can access its details using Alexa.
Keywords: Employee Management system; EMS; AWS; Leave Monitor